Lessons learned: Exploring faculty and field instructor perceptions of student writing abilities and needs - Marcus Crawford; Travis Cronin; Dheeshana Jayasundara; Randy Nedegaard (Journal of Social Work Education and Practice)
Writing is recognized as an important skill for professional social workers across the diversity of practice areas. An integral part of the communication about writing expectations is clarifying and defining the purpose and goals of the writing assignments in the course.  This paper discusses the findings associated with perceptions and expectations of teaching faculty and professional social workers who served as field instructors in the program. To accomplish this, we conducted a survey of all faculty, both part-time and full-time, and all field instructors serving in the program. Results from our surveys showed perceptions of student writing deficits among faculty and field instructors. During the project, key needs emerged, including ongoing faculty development; strategies for incorporating part-time faculty in efforts to support student writing; clearer articulation of the difference between academic and professional writing and the purpose of teaching academic writing in professional training; more communication among faculty, students, and practitioners about the writing skills needed for impactful social work practice. Implications and future directions for the department are discussed.